STRATEGI RETENSI GURU BERKUALITAS MELALUI PENDEKATAN HUMANISTIC MANAGEMENT DI SEKOLAH - Muvtia Agustina; Zainal Berlian; Baharudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze strategies for retaining qualified teachers through a humanistic management approach in schools to ensure sustainable educational quality and organizational stability. The research employed a qualitative case study design, with data collected through in-depth interviews, observations, and documentation, and analyzed using thematic techniques. The findings indicate that teacher retention is influenced not only by financial factors but also by empathetic leadership, job satisfaction, supportive organizational culture, and opportunities for professional development. The humanistic management approach effectively creates a work environment that respects individual dignity, encourages active participation, and supports teachers’ psychological well-being. Participative and communicative school leadership plays a crucial role in strengthening organizational commitment and teacher loyalty, while a positive organizational culture and continuous professional development enhance teachers’ emotional attachment to the institution. Therefore, effective teacher retention strategies require a holistic approach grounded in human values to improve satisfaction, commitment, and the overall quality of education sustainably.